Penjadwalan Mata Kuliah Otomatis Menggunakan Algoritma Late Acceptance Hill-Climbing Hyper-Heuristics dengan Domain Permasalahan ITC - Cut Alna Fadhilla (LKP Unity Academy, 2024)
The International Timetabling Competition is an international scheduling competition that aims to motivate further research on scheduling issues especially in scheduling in the field of education. In the world of education, scheduling problems have become a topic that is often encountered. One of the scheduling problems found in higher education is scheduling courses. Course scheduling is conducted routinely at the beginning of each semester, in scheduling must pay attention to the allocation of resources contained in the university. Scheduling is a long process, it is because in allocating resources in a scheduling problem must pay attention to various aspects or limits that have been set in order to get optimal results. This problem is classified as a Non-Polynomial hard problem, where there is no exact algorithm to solve it in a polynomial time. In the preparation of this final project subject scheduling is done using a tabu search algorithm - simulated annealing hyper-heuristics. The dataset used is a dataset obtained from the 2019 International Timetabling Competition. The results of this final project are java-based automatic scheduling applications which are expected to help solve problems related to scheduling subjects more optimally, and solutions that are produced competitive with benchmark algorithms.